Screening for anxiety and depressive symptoms in adolescents in the Covid-19 pandemic: a scoping review protocol (Research, Society and Development, 2022)
Objective: to develop a scope review protocol to map symptoms of anxiety and depressive disorders in adolescents in the context of the Covid-19 pandemic. Methodology: The construction of the protocol was based on the Joanna Briggs Institute manual and adopts the Prefered Reporing Items for Systematic Review and Meta-Analyses - Extension for Scoping Reviews checklist and was registered in the Open Science Framework under No. osf.io/j76ga. The research and data collection will take place in October 2022 using Health Science Descriptors and Boolean operators AND and OR in the search equation ((Adolescent OR Adolescence OR Teen OR Teenager) AND (“Psychic Symptoms” OR Depression OR Anxiety OR “Anxiety Disorders” OR “Mental Symptoms” OR “Depressive Symptom” OR Angst) AND (“Covid-19”). The choice of studies will be carried out by two researchers independently. For the interpretation of results and analysis, the Statistical Package for Social Sciences software will be used.